Implementation Of The Package C Education Program For Takhassus Students at The Tahfidzul Quran Misykat Al-Anwar Islamic Boarding School Yogyakarta, Pringsewu, Lampung - Miftahul Jannah; Ulfah Umurohmi; Nur Sukartini (International Journal of Islamic Educational Research, 2024)
In partnership with PKBM Nusa Indah, this study attempts to characterize and assess the execution of the Package C Equivalency Education Program for Takhassus pupils at Pondok Pesantren Tahfidzul Quran Misykat al-Anwar. The curriculum goal is to provide students the chance to complete their primary studies and memorization of the Quran while still earning a credential that is comparable to Senior High School (SMA). Using methods for gathering data including in-depth interviews, documentation, and observation, the study takes a qualitative approach. The head of the pesantren, PKBM tutors, and participating students are among the study's key informants. The findings show that this program is effective in giving Takhassus pupils access to general education that is comparable to SMA, despite a number of obstacles still standing, including a dearth of program socialization among the community and resource constraints for teachers. Students express great satisfaction with this curriculum, especially with regard to gaining academic information that enhances their religious education. Additionally, the earned diploma is accepted across the country, giving students the chance to continue their study or find employment.This study highlights how crucial it is for pesantren and PKBM to work together to provide an adaptable yet high-quality teaching program. It is envisaged that the results would provide a basis for suggestions to the pesantren's management and other pertinent parties to improve the Package C Program's execution and lessen current obstacles in order to improve educational achievements.